Analisis Tingkat Kesesuaian dan Daya Dukung Kawasan Wisata Pantai Osapan, Distrik Demta, Kabupaten Jayapura - Caecilia Paramma; Baigo Hamuna; Efray Wanimbo (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2021)
Osapan Beach is a beach tourism object located in Demta District, Jayapura Regency, which is currently still in the early stages of development to become a tourist spot. However, the existence of Osapan Beach is not widely known by the people in the City and Regency of Jayapura. Until now, there is no data or results of scientific studies that can be used as a reference for the development and management of Osapan Beach in the future. This study aims to determine the level of suitability of the area and carrying capacity and to find out how the perception of the community and tourists in the development of Osapan Beach as an eco-tourism location. This research was conducted from January to June 2021. The methods used in this study include the observation method (observation and direct collection of tourism suitability parameter data), interviews with respondents (asking several questions using questionnaires to 35 respondents and documentation (recording data, taking research drawings/photos). The results showed that the tourism suitability index (IKW) for all ecotourism suitability parameters at Osapan Beach, station 1 and station 2 had the same value, namely 89.28% (Highly Appropriate/S1), station 3 had a value of 95.23% (Very Appropriate/S1) and station 4 has a score of 82.14% (Suitable/S2). The carrying capacity of Osapan Beach as an ecotourism location is 21 people/day. Most of the respondents think that Osapan Beach deserves to be used as an ecotourism area where Osapan Beach has an attraction and has the potential to support the economy of the Yakore Village community. The main thing that needs to be considered in the construction of facilities to support tourism activities.Key Words: Ecotourism; Suitability; Carrying Capacity; Osapan Beach; Demta District